1994
DOI: 10.12693/aphyspola.86.7
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with a Mesomaser

Abstract: We investigated the dynamically modified interaction between Rydberg atoms and a single mode of a microwave cavity driven by a strong external field. With a monochromatic injected field we observed dynamic suppression of spontaneous emission, when the intracavity Rabi frequency exceeds the cavity linewidth. We discuss a theoretical model using non-Markovian decay rates, which is in excellent agreement with experiment. When a bichromatic driving field is used, enhanced decay reappears in narrow resonance zones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For example, the scheme of [15] could be used for this purpose, but with the decreased (at least up to 5 MHz) modulation frequency. The presented results may also contribute to better understanding of experiments of H.Walther and W.Lange [28] on intracavity excitation of an atom by bichromatic field. …”
mentioning
confidence: 65%
“…For example, the scheme of [15] could be used for this purpose, but with the decreased (at least up to 5 MHz) modulation frequency. The presented results may also contribute to better understanding of experiments of H.Walther and W.Lange [28] on intracavity excitation of an atom by bichromatic field. …”
mentioning
confidence: 65%
“…Moreover, a very narrower peak (than before) is imposed on the central peak, a signature of an auxiliary in-phase radiation interference [109]. It has been reported that [116], if the external excitation of the cavity mode is smaller than or comparable to the eld radiated by the atoms, cooperative atomic behavior is expected.…”
Section: Effect Of Turning On the Classical Pumping For Various Detun...mentioning
confidence: 90%
“…In fact, on systems with bichromatic or monochromatic driving, the Hamiltonian is necessarily time dependent. Consequently, the spectra acquires such a complex structure [116]. Therefore, stationary energy levels and steady-state spectra do not exist and all expectations depend on time.…”
Section: Response Of Atomic Emission Spectra To the Classical Pump Onlymentioning
confidence: 99%
See 2 more Smart Citations